Implementation of the Execution of the Fiduciary Guarantee Object After the Decision of the Constitutional Court Number 18 PPU XVII 2019 - Priadinata, Alko; Kirana, Dwi Paksi; Azis, Abdul; Harmono , Harmono; Rahman, Alip (PT FORMOSA CENDEKIA GLOBAL, 2025)
This paper analyzes the application of fiduciary guarantees following the issuing of Constitutional Court Decision Number 18/PUU-XVII/2019. This ruling upholds the debtor's entitlement to legal protection against the wrongful execution of fiduciary obligations that contravene legal stipulations within the framework of Indonesian law. This research employs a normative juridical approach by examining documents and interpreting legal statutes, Constitutional Court rulings, and pertinent field activities. The study's findings indicate that, following the Constitutional Court's ruling on enforcing fiduciary assurances, numerous changes have transpired, particularly on procedural aspects and safeguarding debtors' rights. The current issues are legal ambiguity and the necessity for more comprehensive rules. This report advocates for amending regulations and enhancing law enforcement officers' capabilities to ensure the execution of fiduciary assurances aligns with legal provisions.